1974
DOI: 10.1172/jci107587
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of immunoglobulins with liposomes.

Abstract: A B S T R A C T Liposomes were used as model targets to test the effect of immunoglobulins on biomembranes. Heat-aggregated immunoglobulins (Ig) exceeded native immunoglobulins in their capacity to release anions and glucose from model liposomes (either lecithin-dicetylphosphate-cholesterol or lecithin-stearylamine-cholesterol in molar ratios of 7: 2: 1). This interaction was not dependent upon the presence of cholesterol in the membrane. Mild heat-aggregation (10 min at 61.50C) increased the membrane-perturbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 35 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…Serum-treated zymosan can bind to human PMN via "specific" receptors for the opsonic fragment of the third component of complement which coats these particles (14,15). The reactive site on aggregated IgG appears to reside on the Fc region which can engage and perturb lipid membranes (16). Aggregated IgG may also react with more specific receptors on the cell surface (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Serum-treated zymosan can bind to human PMN via "specific" receptors for the opsonic fragment of the third component of complement which coats these particles (14,15). The reactive site on aggregated IgG appears to reside on the Fc region which can engage and perturb lipid membranes (16). Aggregated IgG may also react with more specific receptors on the cell surface (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Since it is doubtful that the phospholipid surfaces of liposomes constitute a strong endocytic stimulus to the lysosomal system (11), we reasoned that cells might actively ingest enzyme-containing liposomes if these were coated with aggregated immunoglobulin (12,13). We have previously shown that leukocytes will endocytose immune precipitates in heat-inactivated serum (12), and that aggregated immunoglobulins preferentially associate with liposomes (13) (Pharmacia, Stockholm).…”
mentioning
confidence: 99%
“…We have previously shown that leukocytes will endocytose immune precipitates in heat-inactivated serum (12), and that aggregated immunoglobulins preferentially associate with liposomes (13) (Pharmacia, Stockholm). Aliquots of liposomes (5 ml) were applied to 2.5 X 20-cm columns (operating pressure: 20 cm of water) with a flow rate of 0.1-0.5 ml/min; elution was in 0.145 M NaCl-KCl (equimolar) containing 0.05 M phosphate buffer (pH 7.4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the pH of the test media have a significant effect on in vitro activities of macrolides, fluoroquinolones and aminoglycosides but leaving ß-lactams unaffected [25][26][27][28][29]. Furthermore, storage time and freeze-thaw cycles affect the stability of some serum proteins including albumin [30][31][32] and exposure of serum to heat as used for complement inactivation induced conformational changes of serum proteins affecting their interaction with bacterial membranes and antigens [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%